2001
DOI: 10.1074/jbc.m102858200
|View full text |Cite
|
Sign up to set email alerts
|

Noncovalent Interaction between Ubiquitin and the Human DNA Repair Protein Mms2 Is Required for Ubc13-mediated Polyubiquitination

Abstract: Ubiquitin-conjugating enzyme variants share significant sequence similarity with typical E2 (ubiquitin-conjugating) enzymes of the protein ubiquitination pathway but lack their characteristic active site cysteine residue. The MMS2 gene of Saccharomyces cerevisiae encodes one such ubiquitin-conjugating enzyme variant that is involved in the error-free DNA postreplicative repair pathway through its association with Ubc13, an E2. The Mms2-Ubc13 heterodimer is capable of linking ubiquitin molecules to one another … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
162
0
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 128 publications
(177 citation statements)
references
References 41 publications
12
162
0
3
Order By: Relevance
“…Likewise, Xiao et al (32) proposed that in yeast, the Mms2͞Ubc13 complex is required to promote both RAD5-and POL30-dependent error-free replication pathways. Recently, McKenna et al (33) showed that in human cells, hMms2 forms a complex with hUbc13, and this interaction is required for hUbc13-mediated polyubiquitination through Lys-63. The crystal structure of this complex also was determined recently (34).…”
Section: Indirect Evidence That Human Cells Use the Newly Synthesizedmentioning
confidence: 99%
“…Likewise, Xiao et al (32) proposed that in yeast, the Mms2͞Ubc13 complex is required to promote both RAD5-and POL30-dependent error-free replication pathways. Recently, McKenna et al (33) showed that in human cells, hMms2 forms a complex with hUbc13, and this interaction is required for hUbc13-mediated polyubiquitination through Lys-63. The crystal structure of this complex also was determined recently (34).…”
Section: Indirect Evidence That Human Cells Use the Newly Synthesizedmentioning
confidence: 99%
“…We demonstrated here that OsUbc13 physically interacted with OsCROC-1 ( Fig. 5b; Table 1), which is essential for Ubc13-mediated Lys63 polyubiquitylation (Hofmann and Pickart, 1999;McKenna et al, 2001;Wen et al, 2006); this once again implies the existence of error-free DDT in plants and the critical role of OsUbc13 in tolerance to DNA damage during seed and pollen germination.…”
Section: Os08g0199300mentioning
confidence: 89%
“…Conventional poly-Ub via Gly76-Lys48 is the principal signal for proteolysis through 26S proteasomes (Hochstrasser, 1996), while Gly76-Lys63 poly-Ub regulates diverse activities in a non-proteolytic way (Pickart, 2001). So far, Ubc13 is the only known Ubc capable of catalyzing the Lys63-linked polyubiquitylation reaction and this function requires interaction with the Ubc variant (Uev, which shares a similar sequence and structure with the E2 Ub-conjugating enzymes, but lacks the active cysteine residue); thus, it is unlike other Ubc proteins that catalyze a conventional Lys48-linked polyubiquitylation reaction (Hofmann and Pickart, 1999;McKenna et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This observation is understandable, as mammalian Ubc13 interacts with a panel of E3 ligases and is involved in several biological processes in addition to DNA damage responses (Andersen et al, 2005). Since a Uev is absolutely required for Ubc13-mediated Lys63-linked polyubiquitination (Hofmann and Pickart, 1999;McKenna et al, 2001), we suspect that the four AtUEV1 genes may also have distinct as well as overlapping functions, making them unsuitable for the proposed investigation. We turned our attention to plant homolog(s) of Rad5, the yeast cognate E3 ligase of Ubc13 required for error-free DDT (Ulrich and Jentsch, 2000;Xiao et al, 2000), since E3s often provide substrate specificity.…”
Section: Characterization Of Rad5a Rev3 Double Mutantsmentioning
confidence: 99%
“…In contrast to the function in proteasomal protein degradation of target proteins by the K48-linked polyubiquitination, K63-linked polyubiquitination plays diverse non-proteolytic functions (Pickart, 2001). So far, Ubc13 is the only known E2 enzyme capable of catalyzing K63-linked polyubiquitination, which requires an Ubc/E2 variant (Uev) as a co-factor (Hofmann and Pickart, 2001;McKenna et al, 2001). Uev proteins are similar to Ubcs, but lack of a critical Cys residue in the active site.…”
Section: Rad6 and Ubiquitinationmentioning
confidence: 99%